Konstruksi Identitas dan Presentasi Diri Digital Pengguna Aplikasi Kencan Bumble - Stevany, Ester; Utami, Lusia Savitri Setyo (Kiwari, 2025)
The development of digital media has transformed the way individuals build interpersonal connections, including through online dating applications. Bumble provides a virtual communication space that enables users to construct their digital identities strategically through visual and textual elements. This study aims to examine how Bumble users construct their identities and apply self-presentation strategies within application-mediated interactions. The Hyperpersonal Communication Theory and the concept of Affordance are used to understand how selective self-disclosure and platform features shape these processes. This research employs a qualitative approach using a case study method involving Bumble users. The findings indicate that photos function as the primary component in forming first impressions, as they convey lifestyle cues and the visual character users intend to communicate. Elements such as biographies, interest tags, and prompts complement this narrative by highlighting values, preferences, and relational intentions. Self-presentation is carried out selectively, both by emphasizing positive attributes and by withholding information perceived as sensitive or potentially stigmatizing. Users also adjust their profiles continuously to enhance interaction compatibility. These results demonstrate that digital identity on Bumble is flexible, curated, and continually negotiated in accordance with users’ communication goals and preferences. Perkembangan media digital mengubah cara individu membangun koneksi interpersonal, termasuk melalui aplikasi kencan daring. Bumble menyediakan ruang komunikasi virtual yang memungkinkan pengguna membentuk identitas digital secara strategis melalui elemen visual dan tekstual. Penelitian ini bertujuan memahami bagaimana pengguna Bumble mengonstruksi identitas diri serta menerapkan strategi self-presentation dalam interaksi yang dimediasi aplikasi. Teori Komunikasi Hiperpersonal dan affordance digunakan untuk melihat bagaimana selektivitas penyampaian diri dan fitur aplikasi berperan dalam proses tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus terhadap pengguna Bumble. Hasil penelitian menunjukkan bahwa foto menjadi komponen utama dalam pembentukan kesan awal karena mampu menampilkan gaya hidup dan karakter visual yang ingin dikomunikasikan. Elemen seperti biography, interest tags, dan prompt digunakan untuk melengkapi narasi diri dengan menonjolkan nilai, minat, atau tujuan relasional tertentu. Strategi self-presentation dilakukan secara selektif, baik dengan menegaskan aspek positif maupun menyembunyikan informasi yang dianggap sensitif atau berpotensi menimbulkan stigma. Selain itu, pengguna melakukan penyesuaian profil secara berkelanjutan untuk meningkatkan kecocokan interaksi. Temuan ini menunjukkan bahwa identitas digital pada Bumble bersifat fleksibel, kuratif, dan terus dinegosiasikan sesuai preferensi dan tujuan komunikasi.